Emerging Role of LncRNAs in Ischemic Stroke—Novel Insights into the Regulation of Inflammation - Pan Y (Dove Medical Press, 2021)
Yongli Pan,1,* Qingzheng Jiao,2,* Wei Wei,3,* Tianyang Zheng,4,* Xinyu Yang,5 Wenqiang Xin5 1Department of Neurology, Weifang Medical University, Weifang, Shandong, People’s Republic of China; 2Second Department of Internal Medicine, Gucheng County Hospital, Gucheng, Hebei, People’s Republic of China; 3Department of Neurology, Mianyang Central Hospital, Mianyang, Sichuan, People’s Republic of China; 4Department of Neurosurgery, The First Hospital of Jilin University, Changchun, Jilin, People’s Republic of China; 5Department of Neurosurgery, Tianjin Medical University General Hospital, Tianjin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenqiang XinDepartment of Neurosurgery, Tianjin Medical University General Hospital, Anshan Road No. 154, Tianjin, 300052, People’s Republic of ChinaTel +86– 185 26201182Fax +86– 22 60362062Email xinwenqiangdr@126.comAbstract: As a crucial kind of pervasive gene, long noncoding RNAs (lncRNAs) are abundant and key players in brain function as well as numerous neurological disorders, especially ischemic stroke. The mechanisms underlying ischemic stroke include angiogenesis, autophagy, apoptosis, cell death, and neuroinflammation. Inflammation plays a vital role in the pathological process of ischemic stroke, and systemic inflammation affects the patient’s prognosis. Although a great deal of research has illustrated that various lncRNAs are closely relevant to regulate neuroinflammation and microglial activation in ischemic stroke, the specific interactional relationships and mechanisms between lncRNAs and neuroinflammation have not been described clearly. This review aimed to summarize the therapeutic effects and action mechanisms of lncRNAs on ischemia by regulating inflammation and microglial activation. In addition, we emphasize that lncRNAs have the potential to modulate inflammation by inhibiting and activating various signaling pathways, such as microRNAs, NF‐κB and ERK.Keywords: ischemic stroke, long noncoding RNA, microglia, neuroinflammation